Podoplanin expression in lymph node metastases of head and neck cancer and cancer of unknown primary patients. Issue 3 (September 2022) - Kühn, Jan Philipp; Bochen, Florian; Körner, Sandrina; Schick, Bernhard; Wagner, Mathias; Smola, Sigrun; Berkó-Göttel, Barbara; Morris, Luc G.T.; Wang, Jingming; Bozzato, Alessandro; Linxweiler, Maximilian
Introduction: Head and neck squamous cell carcinomas (HNSCCs) are cancers with generally poor prognosis. Outcomes have not improved in decades, with more than half of the patients presenting with lymph node metastases at the time of diagnosis. A unique subtype of HNSCC, cancer of unknown primary of the head and neck (HNCUP) is associated with a poor outcome. Increased expression of the D2-40 gene (podoplanin) has been described for several human malignancies and has been associated with increased metastatic potential of cancer cells. Methods: In order to examine the role of podoplanin in lymph node metastasis of HNSCC generally and HNCUP specifically, we evaluated the prognostic impact of podoplanin expression in HNSCC- (n = 68) and HNCUP-associated lymph node metastases (n = 30). The expression of podoplanin was analyzed by immunohistochemical staining of lymph node tissue samples and correlated with clinical and histopathological data. Results: We found a non-significant tendency towards a higher podoplanin expression in HNCUP compared to HNSCC lymph node metastases and a significant correlation between a high podoplanin expression and advanced node-stage classification. Podoplanin expression had no significant impact on overall survival for both groups and did not correlate with human papillomavirus tumor status. Conclusion: Taken together, our results suggest that upregulation of podoplanin may be associated with a stimulation of lymphatic metastasis in head and neck cancer.